Assessment of the reliability of digital cephalometric analysis using One Ceph app in comparison with manual cephalometric analysis - Khan, Mashal; Rozina Nazir; Ruhamaa Arshad (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate and compare the accuracy and reliability of digital cephalometric tracing against the traditional manual tracing method. Method: The retrospective, cross-sectional study was conducted at the Department of Orthodontics, Foundation University College of Dentistry and Hospital, Islamabad, Pakistan, from January 8 to April 10, 2024, and comprised randomly-selected, good-quality pre-treatment lateral cephalometric radiographs taken from the same imaging machine. The radiographs were subjected to both manual and digital OneCeph tracing methods by a single operator. All the 10 cephalometric variables used in Steiner’s analysis were assessed. Data was analysed using SPSS 21. Results: Of the 60 radiographs assessed, 30(50%) were included; 18(60%) from female patients and 12(40%) from male patients. The overall patient age was 15-40 years. When subjected to both manual and digital tracing, the radiographs showed no significant difference on any of the 10 parameters assessed between the two methods (p>0.05). Conclusion: Digital tracing of lateral cephalometric radiographs could be a reliable alternative to manual tracing. Key Words: App, Cephalometrics, Analysis, Reliability, Cross-sectional study.